Major Depressive Disorder with Sub-threshold Bipolarity in the National Comorbidity Survey Replication - Angst, Jules (2010)
OBJECTIVES: There is growing clinical and epidemiologic evidence indicating that major mood disorders form a spectrum from Major Depressive Disorder (MDD) to pure mania. The present investigation examined the prevalence and clinical correlates of MDD with sub-threshold bipolarity vs. pure MDD in the National Comorbidity Survey Replication (NCS-R). METHODS: The NCS-R is a nationally representative face-to-face household survey of the U.S. population conducted between February, 2001 and April, 2003. Lifetime history of mood disorders, symptoms and clinical indicators of severity were collected using version 3.0 of the WHO Composite International Diagnostic Interview, a fully structured lay-administered diagnostic interview. RESULTS: Nearly 40% of study participants with a history of major depressive disorder had a history of sub-threshold hypomania. This subgroup had a younger age of disorder onset, more episodes of depression, and higher rates of comorbidity than those without a history of hypomania, and lower levels of clinical severity than those with bipolar II disorder. CONCLUSIONS: The findings demonstrate heterogeneity of major depressive disorder and support the validity of inclusion of sub-threshold mania in the diagnostic classification. The broadening of criteria for bipolar disorder would have important implications for research and clinical practice.